2022
DOI: 10.17559/tv-20210705101118
|View full text |Cite
|
Sign up to set email alerts
|

Strength Degradation Characteristics of the Steel-Concrete Interface Under Cyclic Shear

Abstract: The shear capacity of the steel-concrete interface (SCI) of concrete-filled steel tubular piles (CFSTs) degrades due to the cyclic shear action of external loading and unloading and can result in a reduction in the bearing capacity. To explore the shear strength degradation characteristics of the steel-concrete interface under cyclic shear, cyclic shear tests for three roughness types and under four different normal stresses were carried out by using a large-scale repeated direct shear test system. The charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Zhang et al proposed a bilinear shear model to describe the relationship between shear stress and concrete-rock's relative displacement for rock-socketed bored piles in soft rock, elucidating the critical shear displacement at the concrete-rock interface and establishing a load transfer method for soft rock-socketed piles [17]. Based on the indoor shear test, Liu et al showed that the peak SCI shear load increased exponentially with the increase of directional stress and decreased logarithmically with the increase of cyclic shear time [18]. Lei et al found that the shear expansion effect existed in the interface sliding of rock-socketed piles.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al proposed a bilinear shear model to describe the relationship between shear stress and concrete-rock's relative displacement for rock-socketed bored piles in soft rock, elucidating the critical shear displacement at the concrete-rock interface and establishing a load transfer method for soft rock-socketed piles [17]. Based on the indoor shear test, Liu et al showed that the peak SCI shear load increased exponentially with the increase of directional stress and decreased logarithmically with the increase of cyclic shear time [18]. Lei et al found that the shear expansion effect existed in the interface sliding of rock-socketed piles.…”
Section: Introductionmentioning
confidence: 99%